Tissue engineering of vascular/valvular equivalents on the base of the xenogeneic decellularized matrix - Savchuk, M.V. (Вiopolymers and Cell, 2014)
According to the WHO, in 2008 cardiovascular diseases claimed the lives of 17.5 million people (30 % of all diseases). Often the only option to save a patient’s life is a replacing the injured part of an organ by the prosthesis. Aim. This research was aimed to produce biomodificated cardiovascular graft by decellularisation of porcine heart valve. Methods. Our method of decellularization permits to make morphologically and physically non-modified decellularised extracellular matrix. Results. The analysis of matrix shows a decrease of the total number of cells, preservation of the collagen and elastin fibers structure, and safety of physiological adhesion. Conclusions. The matrix can be used as a framework for the vessel-valvular tissue-engineering prosthesis after its recellularization by the recipient’s autologous cells. Згідно з даними ВООЗ, у 2008 році в світі від серцево-судинних захворювань померло 17,5 млн людей (30 % усіх захворювань). Часто єдино можливим варіантом спасіння життя пацієнта є заміна пошкодженої ділянки органа протезом. Мета. Отримання біомодифікованого сердцево-судинного графта за рахунок децелюляризації серцевого клапана свині. Методи. Наша технологія дозволяє отримати морфологічно і фізично не змінений децелюляризований екстрацелюлярний матрикс. Результати. Аналіз матриксу демонструє зниження загальної кількості клітин, збереженість структури колагенових та еластинових волокон, а також фізіологічної адгезивності матриксу. Висновки. Матрикс після децелюляризації є придатним для використання як каркаса для судинно-клапанного тканинно-інженерного протезу після його рецелюляризації аутологічними клітинами реципієнта. Согласно данным ВОЗ, в 2008 году в мире от сердечно-сосудистых заболеваний умерли 17,5 млн человек (30 % всех заболеваний). Часто единственно возможным вариантом спасения жизни пациента является замена поврежденного участка органа протезом. Цель. Получение биомодифицированного сердечно-сосудистого графта вследствие децеллюлирования свиного сердечного клапана. Методы. Наша технология позволяет получить морфологически и физически не измененный децеллюлированный экстрацеллюлярный матрикс. Результаты. Анализ матрикса демонстрирует снижение общего количества клеток, сохранность структуры коллагеновых и эластиновых волокон, а также физиологической адгезивности матрикса. Выводы. Таким образом, матрикс является пригодным для использования его в качестве каркаса сосудисто-клапанного ткане-инженерного протеза после рецеллюляризации аутологичными клетками реципиента.